Expressão imuno-histoquímica da triptase em mastócitos nos fibromas de células gigantes e hiperplasias fibrosas de mucosa oral - Santos, Pedro Paulo de Andrade (2008)
The giant cell fibroma is a benign neoplasm characterized by the presence of mono, bi or multinucleate cells, which can have a connection to the presence of mast cells. This research aims to analyze, descriptively and comparatively, the immunohystochemistry expression of the tryptase in mast cells of the giant cell f ibroma, f ibrous hyperplasia and samples of the normal oral mucosa. Thirty cases of giant cell fibroma, ten cases of fibrous hyperplasia and ten cases of normal oral mucosa were selected for the analysis of the immunohistochemistry expression, determination of the number of present mast cells, as well as their location and shape. It could be stated that there was a statistically signif icant difference (p<0,001) in relation to the quantity of mast cells among other samples analyzed where the giant cell f ibroma presented lesser quantity of mast cell and the hyperplasia showed higher concentration of this cellular type. Although the oral mucosa has presented a higher quantity of mast cells when compared to the giant cells fibroma, these were found in usual locations in the connective tissue in normal tissues. There could be noticed a statistically significant difference in relation to the number of non-granulated mast cells (p<0,001). On the areas of fibrosis, we could observe a statistically signif icant difference (p<0,006) among the samples. In relation to the present mast cells in perivascular location, no statistically signif icant difference was found. On the morphological analysis there was a predominance of oval mast cells. It was concluded that despite of the fact there was a lesser quantity of mast cells present in cases of giant cell f ibroma, they appeared to have a stronger relation to the present giant fibroblasts in this lesions, around 59,62%, being also evidenced a strong relation between these cells and the fibrosis areas in both cases of giant cell f ibroma and f ibrous hyperplasias and samples of normal oral mucosa, used as control group in our study, confirming, this way, the role of the mast cells as fibrinogenous inductor